2012
DOI: 10.1002/nau.22249
|View full text |Cite
|
Sign up to set email alerts
|

Double incontinence in a cohort of nulliparous pregnant women

Abstract: Symptoms of double incontinence are prevalent during first pregnancy; age and other intrinsic factors may favor the occurrence of double incontinence throughout gestation, while instrumental delivery and episiotomy increase the risk of double incontinence in the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Furthermore, through Epi-no, it is also possible to evaluate the real need for episiotomy and prevent its indiscriminate use, thereby protecting the patient from complications such as perineal pain in the immediate postoperative period and dyspareunia in the late puerperium. In addition, studies have shown that episiotomy does not protect women from the risk of urinary and fecal incontinence [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, through Epi-no, it is also possible to evaluate the real need for episiotomy and prevent its indiscriminate use, thereby protecting the patient from complications such as perineal pain in the immediate postoperative period and dyspareunia in the late puerperium. In addition, studies have shown that episiotomy does not protect women from the risk of urinary and fecal incontinence [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy highlights the importance for more research on this topic to define precise guidelines for this common procedure. Furthermore, some previous studies reported that episiotomy use was additionally associated with higher rates of obstetric complications, comprising advanced perineal tears, postpartum haemorrhage, pain and urinary and anal sphincter incontinence [9][10][11][12]. Despite higher failure rates than when the conventional vacuum is used, the Kiwi omnicup is nowadays the most commonly used vacuum device at our department [13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…8,9 Moreover, this procedure can be related to a higher, rather than lower, incidence of advanced perineal tears. 10,11 Thus, the objective of our study was to perform a metaanalysis of the existing literature examining the effectiveness of episiotomy in the prevention of advanced perineal tears, and other maternal and neonatal complications, at the time of vacuum delivery.…”
Section: Introductionmentioning
confidence: 99%